PENGEMBANGAN MODEL LAYANAN REHABILITASI KARYA BERWAWASAN LINGKUNGAN BAGI PENYANDANG CACAT - Munzayanah Munzayanah; Abdul Salim (PAEDAGOGIA, 2009)
Until recently, the government faced the problems of the handicapped's labor force. The management of handling those problems is much more complex than that of normal unemployment. The complexity is indicated by the following issues: (a) vacancies,(b)skillsmastery,(c)highrequirementstogetajob,and(d)theinternalinterference of the handicapped's conditions. Based on these facts, the program of occupational rehabilitation service is crucial. This research aims to develop a model of occupational rehabilitation service based on environment view for the handicapped people. This research is also aimed at (a) figuring out the difference of their skill mastery before and aftertreatmentand(b)knowingthefeasibilityoftheappliedmodel.Themodelcomprises of (1) screening, (2) assessing and classifying the handicapped children and environment, (3) planning occupational rehabilitation program, (4) implementing the program, (5)evaluating,(6)placementandfollowup.ThisresearchisconductedinSurakarta.The subjects, 20 persons who graduate from junior and senior of special schools (SLTP and SMLB), were taken purposively as sample. To collect the data, the methods of observation, interview, test, and document are used. The data then were analyzed through qualitative descriptive, descriptive statistic, and non parametric statistic. The result of the research showed that (a) the model of environment based on occupational rehabilitation was feasible; (b) there was a significant difference of the handicapped children's skillmasterybeforeandaftertreatmentwithlessthan1%error.